2017
DOI: 10.4172/2380-2391.1000207
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Biochar on the Agriculture and Environment - A Review

Abstract: The agricultural soil or land is fertilized using fertilizers (natural or synthesized).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 26 publications
0
16
0
1
Order By: Relevance
“…In addition, Jeffery et al (2011) in a meta-analysis indicated biochar-treated soils increased crop productivity averagely at 10% (-28% to 39%) compared with plots without mulching. Residual impact of biochar on soil fertility largely accounted for an increase in crop yield under co-application of plastic film mulched ridge-furrow with biochar treatment (Rehman & Razzaq, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Jeffery et al (2011) in a meta-analysis indicated biochar-treated soils increased crop productivity averagely at 10% (-28% to 39%) compared with plots without mulching. Residual impact of biochar on soil fertility largely accounted for an increase in crop yield under co-application of plastic film mulched ridge-furrow with biochar treatment (Rehman & Razzaq, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, agricultural residues with high carbon content, such as palm shell, coconut coir, and rice husk have been studied as potential alternative adsorbents for AC (Sun et al, 2013;Ahmad et al, 2014;Mook et al, 2016;Mi et al, 2016). Typically, they can be applied to produce biochar by thermal degradation in oxygen-limited conditions, and consequently utilized as a low-cost adsorbent for pollutant separation from air, or heavy metals as well as textile dye removal from wastewater (Mi et al, 2016;Moazzam et al, 2017;Rehman and Razzaq, 2017). Biochar adsorption has been intensively studied because it has excellent adsorption capability and satisfies the need for cost effective adsorbents.…”
Section: Introductionmentioning
confidence: 99%
“…It can be used to enhance degraded soils so that they can be utilized for agricultural production that helps mitigate the effects of climate change (Lehmann & Joseph, ). Many studies have shown the beneficial effects of biochar on soil properties such as pH (Masulili, Utomo, & Syechfani, ), nutrient availability (Chan, Van Zwieten, Meszaros, Downie, & Joseph, ), nutrient retention, microbial properties (Rehman & Razzaq, ), and hydrological properties (Sandhu & Kumar, ). Due to its higher surface area and pore space, biochar provides habitat for soil microbes that are beneficial for soil health and helps in nutrient retention by binding important anions and cations (Rehman & Razzaq, ).…”
Section: Introductionmentioning
confidence: 99%